Penerapan Corporate Social Responsibility (CSR) dan Manfaatnya Bagi Perusahaan - Ni Ketut Sri Ardani; Luh Putu Mahyuni (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTThis study aims to find out how the application of Corporate Social Responsibility and benefits to the company's in the Toya Devasya. This study used qualitative research methods. The data collection technique used is using the interview method and documentation. Data analysis used the Miles and Huberman Model data analysis techniques, which consisted of data reduction, data presentation and conclusion drawing. The results showed that the Toya Devasya implemented Corporate Social Responsibility based on Tri Hita Karana. Where Tri Hita Karana contains a meaning that is very complex because each element reflects the things that need to be implemented by each company. The company views that the implementation of Corporate Social Responsibility is important because it is a solution to the impact of business activities caused by the implementation of Corporate Social Responsibility carried out by the company that has been well received by the surrounding community. From the implementation of Corporate Social Responsibility it shows the existence of benefits that can be received by the company such as support from the community and comfort while working perceived by employees. The awareness that the company has to implement Corporate Social Responsibility will have a big impact on the company. The harmony created between the company, society and the environment is one of the impacts that will be felt by the company in carrying out its business activities. This harmony will have an effect on the company's image in the eyes of the community. The company will get support and be recognized in the environment around the company. Because of maintaining a good relationship with the surrounding environment, the community will voluntarily give their support to the Toya Devasya such as promoting the existence of the company to tourists so that there will be an increase in the number of visitors that will affect income.